Role and Behavior of Parents Against the Dental and Oral Health in Children 6-10 Years Old - Sainuddin Sainuddin; Muhammad Saleh; Bahtiar Bahtiar; Sulaeha Sulaeha (Aloha International Journal of Health Advancement (AIJHA), 2021)
Dental and oral health is closely related to knowledge, attitudes, and behavior. The environment plays a very important role in the formation of attitudes and behavior for school-age children. The immediate environment where school-age children are located is the family (parents and siblings) and the school environment. The role of parents and teachers is very decisive in changing attitudes and behavior in the maintenance of children's dental and oral health. The purpose of this study was to analyze the role and behavior of parents in order to maintain dental and oral hygiene in children aged 6-10 years. This study was a literature review. Information obtained from text books, journals, books and other literature. The information is collected and processed by the steps of editing, organizing and interpreting. Based on the results of the study it can be concluded: 1) Parents are examples and role models that can be imitated by children, one of which is in maintaining dental and oral health. Therefore, the role of parents is very important and very large in maintaining dental and oral health in children. The effect on the incidence of caries in children is influenced by knowledge, awareness, and habits of parents in caring for children's dental and oral health. 2) The role of parents in maintaining the health of their children's teeth and mouth is to teach children how to brush their teeth properly, namely brushing their teeth 2 times a day every morning after breakfast and at night before going to bed, taking children to the dentist every 6 months, and also giving education about good food and drink to maintain the health of children's teeth and mouth. 3) Parental behavior towards children's dental and oral health is divided into two, namely open behavior and closed behavior. Where closed behavior refers to parental attention, perception, knowledge/awareness, and attitudes. While open behavior is a form of action/practice of closed behavior. Keywords: dental and oral health; parents; role; behavior